Human papillomavirus causing tonsillar hypertrophy in non-cancerous tonsil - Bakshi, Satvinder Singh; Kaipuzha, Ramiya; Gopalakrishnan, Surianarayanan; A, Govindarajan (The European Research Journal, 2017)
Human papillomavirus (HPV) is associated with the development of most anogenital carcinomas, including cervical cancer and, has more recently been suggested to be a risk factor for a subset of head and neck squamous cell carcinoma. A 15-year-old female presented with complaints of chronically progressive pain on swallowing. Examination revealed bilateral Grade III tonsillar enlargement with multiple warty appearances over the surface of the tonsils. She underwent tonsillectomy and histopathologic study revealed tonsillar crypts lined by stratified squamous epithelium with focal koilocytic changes. Polymerase chain reaction study detected HPV 11 DNA. The presence of HPV in the oral cavity and upper respiratory tract mucosa is of great importance, since several studies have demonstrated an association of HPV with a great variety of benign and malignant lesions. A rare case of benign papillomatosis of the tonsil is presented in this study. There is a need for long-term follow-up due to the possibility and risk factors for malignant transformation.